Fluorescent organic nanoparticles with enhanced fluorescence by self-aggregation and their application for detection of Fe3+ ions. (21st March 2018) - Azadbakht, Reza; Hakimi, Mohammad; Khanabadi, Javad
Abstract : The chemosensor L has a detection limit of 5.57 nM for Fe 3+ in a DMF/H2 O (9 : 1, v/v) mixture. Abstract : In this study, we report a highly stable fluorescent organic nano-chemosensor based on a N3 O2 -macrocyclic ligand. The chemosensor shows very high selectivity and sensitivity towards Fe 3+ ions over other metal cations such as Na +, K +, Cs +, Mg 2+, Ca 2+, Ba 2+, Al 3+, Mn 2+, Fe 2+, Co 2+, Ni 2+, Cu 2+, Zn 2+, Cd 2+, Ag +, Hg 2+ and Pb 2+ ions in aqueous buffer solution.